Implementation of Ball Screw Drive Mechanism in MRT Putrajaya Line Platform Screen Door - Jafri, Muhammad Faris Ikhwan; Nagarajoo, Karthigesu A/L (Progress in Engineering Application and Technology, 2022)
A platform screen door with a belt system was used on the Putrajaya Line. This method has several drawbacks and adds to a number of issues when the door is opened and closed. Maintenance is difficult due to the tight area and location of the belt system. As a result, if a problem with the belt or motor arises, it takes longer to resolve. The belt needs to be adjusted as well, as it may loosen with time. To overcome this difficulty, a direct drive mechanism is now being tested at certain Toei Line stations in Japan as a model. This project will compare the two types of drive mechanisms with the goal of developing a new drive mechanism for the Putrajaya Line.